The role of cultural pluralism in Indigenous peoples’ defense of nature’s rights - Mohammadreza Jodyvash (Oñati Socio-Legal Series, 2025)
Ecuador, by incorporating the Rights of Nature into its constitution, has presented an innovative approach to environmental protection, recognizing nature as a subject with rights. This legal transformation emphasizes the intrinsic value of ecosystems and affirms the right of natural entities to exist, grow, and regenerate. Alongside this, the rights of Indigenous peoples, as guardians of biodiversity, have been strengthened, and their deep connection to ancestral lands is formally recognized. However, the implementation of this legal framework faces challenges, primarily stemming from the conflict between economic priorities and environmental protection. Deforestation in the Amazon, intensified by resource extraction and infrastructure development, poses a threat to global climate balance. Despite international and Indigenous efforts to counter this trend, ineffective law enforcement continues to hinder sustainable conservation. This article, through a dogmatic and analytical approach, concludes that improving this situation requires the development of legal mechanisms, increased participation of Indigenous communities, and a redefinition of economic growth with an emphasis on the long-term health of the planet.